Of Sound Mind and Body: Exploring the Diet-Strength Interaction in Healthy Aging - Askow, Andrew T.; McKenna, Colleen F.; Box, Allyson G.; Khan, Naiman A.; Petruzzello, Steven J.; De Lisio, Michael; Phillips, Stuart M.; Burd, Nicholas A. (Frontiers in Nutrition, 2020)
Strength is a vital component of healthy aging. However, ‘strength’ comes in different forms (includes both physical and mental aspects) and can look different at various phases of adult life. Healthy eating and regular exercise are clearly important pillars for strength. This paper proposes a framework that underlines the value of protein foods and resistance exercise for aging strong.